PERENCANAAN KOMUNIKASI PEMASARAN URBAN QURBAN SEBAGAI PIONEER DALAM INOVASI IBADAH QURBAN - Darmawati, Widya; ., Saepudin (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2014)
Some of marketing experts argue that market pioneering is very important for de-termine long term success of company, market, and product. By being the first to introduce and market the product, pioneer can enjoy sustainable advantage in terms of market share, distribution access, brand familiarity, brand loyality, economies of scale, profit potential, and industry quality standard. However, to achieve those objectives the pioneer needs big effort to enter the market. Urban Qurban, the first qurban through digital platform, implemented Integrated Mar-keting Communication in introducing their brand and product to market. All of promotion programs are designed in creative and measurable marketing commu-nication planning.